Framing the first Palestinian general elections by Malaysia’s New Straits Times - Mohammed Fadel Arandas,; Chang, Peng Kee; Emma Mohamad,; Syed Arabi Idid, (Penerbit Universiti Kebangsaan Malaysia, 2019)
The main focus of this study is the coverage of New Straits Times (NST) of the first Palestinian General Elections for two presidential candidates namely, Yasser Arafat and Samiha Khalil. This study aimed to explore if any of Entman’s 1993 framing functions was used in the coverage of this issue and to explore whether the tone of NST coverage was negative, positive, balanced or neutral. To achieve the aims of this study, qualitative content analysis of elections stories from NST has been adopted. The number of news stories was eight, and the time frame started from 19th January to 13th February 1996, where three of these stories were published on the same day of 22nd January, two days after holding the elections on 20th January. Defining problems and diagnosing causes were the most prominent of Entman’s four framing functions presented in all the articles. The moral judgment function was included in four news stories, and suggesting remedies was included in two news stories out of eight. The findings revealed that Yasser Arafat received 50% balanced coverage, followed by 37.5% positive coverage, and only 12.5% negative coverage, while Samiha Khalil received 67% balanced coverage, compared to 33% positive coverage.